PERAN BRAIN ROT, MOTIVASI BELAJAR, DAN MINAT BACA DALAM MEMBENTUK KEMAMPUAN BERPIKIR KRITIS MATEMATIS MAHASISWA - Netriwati; Fortuna Wati , Mentari; Riskiana Dewi, Novian; Nendra, Fadly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The phenomenon of brain rot, characterized by a decline in cognitive engagement due to excessive consumption of digital content, has become a concern in higher education as it potentially affects students’ learning motivation, reading interest, and critical thinking ability. This study aims to analyze the effects of brain rot, learning motivation, and reading interest on students’ critical thinking ability. This research employed a quantitative non-experimental approach with an ex post facto design. The population of the study consisted of students of the Mathematics Education Program at UIN Raden Intan Lampung, with a sample of 149 students selected through cluster random sampling. Data were collected through a critical thinking ability test and questionnaires on brain rot, learning motivation, and reading interest, and were analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that brain rot, learning motivation, and reading interest simultaneously have a significant effect on students’ critical thinking ability, with brain rot having a negative effect, while learning motivation and reading interest have positive effects. These findings highlight the importance of managing digital content consumption wisely and strengthening learning motivation and reading interest as part of efforts to enhance the quality of students’ critical thinking in higher education.